Novel model of double transgenic mouse results in autoimmune diabetes in males. (17th August 2016) - Chabot, Sylvie; Alvarez, Fernando; Amrani, Abdelaziz; Djilali-Saiah, Idriss
Abstract: Identifying the type of diabetogenic CD8 + T cells that initiate autoimmune diabetes (AID) is a critical step in designing appropriate strategies for the early detection of beta cell-directed autoimmunity and its progression to diabetes. We generated a novel double transgenic (Tg) mouse model on the naturally diabetes resistant C57Bl/6 background, co-expressing two transgenes including a specific TCR anti-lymphocytic choriomeningitis virus nucleoprotein (LCMV-NP) carried by CD8 + T cells and LCMV-NP (as neo-self antigen) expressed by pancreatic beta cells. The resulting double Tg mouse showed partial thymic deletion of the NP-specific CD8 + T cells. The escaping autoreactive NP-specific CD8 + T cells joining the periphery were activated and gained effector functions. Both male and female mice mounted anti-NP antibodies, but only one-fourth adult males spontaneously developed AID. Significant upregulation of the CD44 and CD122 markers as compared to healthy male and female mice characterized the phenotype of diabetogenic CD8 + T cells in diabetic male mice. We also show that only 10% of these CD8 +   T cells expressed programmed death 1 receptor (PD-1). Together, these results suggest that in our double Tg mouse model, Ag-specific effector CD44 + CD122 + PD-1 − CD8 + T cell subpopulation is associated with the pathogenesis of AID.